Unmanned Surface Vehicle (USV) for Water and Aquatic Pollution Monitoring Using IoT - Haizol, Afif Najmi; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2024)
Water pollution is a very important issue because of its direct impact on human life, animals, and ecosystems. The pandemic situation made it difficult to conduct the testing in the actual water bodies such as rivers, lakes, and seas. Although the water drone in that work has been developed that can be controlled remotely, it is only able to record the water temperature. Therefore, an Unmanned Surface Vehicle (USV) for Water and Aquatic Pollution Monitoring using IoT is proposed in this work to improve the previous work by adding a turbidity sensor, total dissolved solids (TDS) sensor and E-201-C pH electrode probe sensor. The USV was used to collect and record water quality readings in terms of turbidity in NTU, TDS in ppm and pH at three different locations in the morning, evening and night. The three locations are the lake in front of the FKEE building, the lake in front of the Development and Maintenance Office UTHM and the watershed at Taman Universiti, Parit Raja. The duration of each experiment is approximately one hour with data taken for every 15 seconds and the data are sent to ThingSpeak application to be displayed for continuous monitoring and stored in its database. The data from ThingSpeak application are then exported to Microsoft excel to plot the graphs, which also calculates the average values. These averages are mapped onto the corresponding NTU scale, TDS level and rating, and pH scale. The turbidity was generally found to be higher at night, while the TDS was highest in the morning at the lake in front of the Development and Maintenance Office UTHM and in the evening at the lake in front of the FKEE building. The pH values varied, being highest in the evening at the lake in front of the FKEE building and the lake in front of the Development and Maintenance Office UTHM, and at night at the watershed at Taman Universiti, Parit Raja. These results indicate that the USV’s sensors provide reliable measurements for monitoring water and aquatic pollution. The variations in the measurements can be attributed to factors such as weather conditions, algae activity, and changes in water temperature. Therefore, it is shown that the USV provides a valuable tool for continuous monitoring of water and aquatic pollution.